2017
DOI: 10.1111/dom.12881
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the increase in ketone concentration during SGLT2 inhibition in NGT, IFG and T2DM patients

Abstract: Results of the present study demonstrate that SGLT2 inhibition exerts different metabolic effects in non-diabetic individuals as compared to diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 18 publications
5
55
1
Order By: Relevance
“…Thus, we could hypothesize only concerning the potential mechanism(s) by which pioglitazone prevents an increase in plasma ketone concentration (Figure ). Previous studies from our group and others have demonstrated an increase in plasma FFA concentration and total body fat oxidation following initiation of SGLT2i therapy.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, we could hypothesize only concerning the potential mechanism(s) by which pioglitazone prevents an increase in plasma ketone concentration (Figure ). Previous studies from our group and others have demonstrated an increase in plasma FFA concentration and total body fat oxidation following initiation of SGLT2i therapy.…”
Section: Discussionmentioning
confidence: 53%
“…We and others have shown that, in addition to lowering plasma glucose concentration, SGLT2i exert multiple other metabolic actions in T2DM patients including improved insulin sensitivity, enhanced beta cell function, and increased plasma free fatty acid (FFA) concentration, total body fat oxidation and ketone production. Although, in absolute terms, the increase in plasma ketone concentration is small, from approximately 0.2 mM to approximately 0.4 mM, it occurs in the vast majority (>90%) of patients receiving SGLT2i therapy,, and in 10% to 20% of patients the plasma ketone level exceeds the upper limit of the normal range . Because of the reduction in daily insulin dose, the increase in plasma ketone concentration associated with the initiation of SGLT2i therapy was highest in patients receiving insulin therapy.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with diabetes have different ketone body homeostasis compared with non‐diabetics . In the former, baseline serum BHB levels were elevated compared with the latter, who also have a higher rate of ketone utilization and production . Conditions such as type 2 diabetes, characterized by a deprivation of glucose utilization, lower insulin‐to‐glucagon ratio, and increased circulating FFAs by accelerated lipolysis, can enhance ketogenesis .…”
Section: Discussionmentioning
confidence: 86%
“…12 Glucagon release by pancreatic -cells is increased following SGLT2 inhibition, which may be beneficial in heart failure through its ionotropic effects, 13 but also increases availability of circulating ketones, thereby providing organs that are critically challenged by hypoxia or ischaemia are provided with an advantageous energy substrate in which to synthesise ATP with reduced oxygen consumption as compared to glucose or fat, as postulated by Ferrannini and others. 14,15 Very little experimental data is currently available to support this hypothesis as an explanation for the advantageous outcomes in EMPA-REG and CANVAS, but it presents an intriguing avenue for further exploration.…”
Section: ) Glucagon and Metabolic Substrate Switching Towards Ketonesmentioning
confidence: 97%